Synthesis and characterization of two 2-amino-5-alkyl-1,3,4-thiadiazolyl carbamate ligands and their Co(II), Ni(II), and Zn(II) complexes - Görgülü, AO; Çukurovali, A (Marcel Dekker Inc, 2002)
Two novel monodentate carbamate ligands derived from 2-amino-5-methyl-1,3,4-thiadiazole and 2-amino-5-ethyl-1,3,4-thiadiazole, have been prepared. The metal complexes of the ligands were prepared with the chlorides of Co(II), Ni(II) and Zn(II) in methanol as solvent. The ligands and their metal complexes have been characterized by elemental analyses, IR, C-13 and H-1 NMR spectra, and magnetic susceptibility measurements. All of the complexes are mononuclear. Thermal properties of the ligands and their complexes have been studied by thermogravimetric analyses (TGA) and differential scanning calorimetry (DSC).